Security Threats from Nuclear Power Plants in War - Wang, Yixuan (International Journal of Social Sciences and Public Administration, 2024)
There are many factors that threaten human safety, and nuclear pollution is one of them. The Russian-Ukrainian war is still going on, and nuclear facilities such as Ukrainian nuclear power plants are inevitably attacked in the war. The security threat of war to nuclear power plants cannot be underestimated. This article will review the security threat of nuclear power plants to humans in war from two aspects: the threat of nuclear accidents to human safety and the impact of war on the safety of nuclear power plants. And look forward to how to respond to this security threat.